Efek Giberelin (GA3) Terhadap Perkecambahan dan Pertumbuhan Cabai Rawit (Capsicum frustescens L.) - Syafii, Mohammad; Mawarda, Revina Ade; Umam, Choirul (Rekayasa, 2024)
Chilli pepper (Capsicum frutescens L) is an important horticulture in Indonesia. High demand often did not meet the production. One of the leading factors is the quality and bad seed conditions, which affect plant growth and production. This research was conducted from February to May 2024 in the research field and laboratory of Plant Breeding and Biotechnology, Agroecotechnology Study Program, Faculty of Agriculture, University of Trunojoyo Madura. The research aim was to determine the effect of gibberellin concentrations and varieties on the germination and plant growth of chili peppers. Factorial randomized Block Design (RBD) was used in this research with gibberellin as the first factor G0 (0 ppm), G1 (1.07 ppm), G2 (1.10 ppm), G3 (1.23 PPM), and the second factor was varieties including V1 (Bhaskara), V2 (Master), V3 (Viral). The data obtained from this experiment was analyzed with analysis of variance (ANOVA) at a 5% level of confidence, and if there were significant differences, the Duncan multiple range test (DMRT) was performed. This experiment showed that G0 and V1 had the best responses to germination and plant growth compared to the other treatments. Furthermore, this showed that gibberellin, the range of treatments, is still ineffective in increasing the germination ability and the growth of chili peppers.